Value Chain Analysis of Large Red Chili (Capsicum Annuum L.) in Jember Regency - Astutik, Diar Fidi; Kustiari, Tanti; Djamali, R.A. (Budapest International Research and Critics University, 2023)
Large red chili (Capsicum annuum L.) is one of the leading vegetable commodities which has a strategic role in the structure of national economic development. According to the Central Statistics Agency, in 2021 there will be an increase in red chili production in East Java Province. Jember recorded a harvest of 6,083 tons with a harvest area of 549 Ha. The increasing market demand is not accompanied by sufficient production, resulting in fluctuating red chili prices. Chili farmers in Andongsari often experience problems marketing fresh products, low selling prices during the main harvest of the harvest due to damage during storage. For this reason, the Larasati Women's Farmers Group (KWT) in Andongsari took the initiative to process large red chilies to increase added value and also extend shelf life by drying them. The business of processing chilies into dried chilies is still considered less promising, so KWT Larasati is making efforts to diversify its processed chili products into various processed chili products. This research was conducted to analyze the chili business value chain to increase sales according to sales targets. Based on data used for one month of production, the tuna variant of simbok chili sauce has the highest added value compared to shredded chilies, this is due to the higher frequency of sales of simbok chili sauce so it has a high resale value.